Effects of different ranges of loads on physical performance using velocity-based resistance training - Riscart-López, J.; Sánchez-Valdepeñas, J.; Colomina-Clemens, F.; Crespo-García, E.; de Castro-Maqueda, G.; Rosety-Rodríguez, M. Á.; León-Prados, J. A.; Pareja-Blanco, F. (Sports, 2025)
(1) Background: The range of loads is defined as the difference between the highest and the lowest relative load (i.e., %1RM) used throughout a resistance training program. However, the optimal range of loads has not been studied yet. Thus, the aim of this study was to compare the effects of different ranges of load (from 50 to 85% 1RM (R50-85), from 55 to 75% 1RM (R55-75), and from 60 to 70% 1RM (R60-70) on physical performance using velocity-based resistance training (VBT).